Delamination assessment in drilling basalt/carbon fiber reinforced epoxy composite material - B.R.N. Murthy (Journal of Materials Research and Technology, 2020)
The present work aims at assessing the delamination damage occurring in a hybrid composite material during the drilling process. The hybrid composite selected for work comprises of basalt and carbon fibers as reinforcements and epoxy as the matrix. Process parameters quantified by speed, feed, and drill size are the selected input independent variables. The response variable, delamination factor (Fd), for each experimental combination, is determined using the simple Chen's one-dimensional equation. Taguchi's L27 orthogonal array (OA)-based experimental design with the ‘smaller-the-better’ approach forms the base for experimental runs and optimization in the present work. ANOVA is applied in the present work to investigate the significance of the linear, squared, and interaction effect of speed, feed, and drill diameter on the delamination damage. Besides, the regression prediction model is developed and validated through a set of confirmation experiments. The optimum process parameters in the drilling of hybrid composite concerning delamination are drill diameter (D) of 6 mm, speed (N) of 1250 rpm and feed rate (f) of 50 mm/min. The regression model developed shows a high degree of fitness with both R-sq and R-sq (adj) values above 80%. The results of confirmation experiments show that the predicted model is highly adequate and there exists only an average prediction error of approximately 2%.